Anemia Prevention Education Through A Combination of Animated Video Media and Digital-Based Literacy Media (CANVA) on Adolescent Girls' Behavior - Filman Afrian Badu; Herlina Jusuf; Djuna Lamondo (Indonesian Journal of Global Health Research, 2025)
Adolescents are individuals undergoing significant development. The nutritional intake required by adolescents varies to achieve balanced nutrition, but if not met, it can lead to various health problems, such as anemia. Anemia is one of the health issues commonly experienced by adolescent girls, especially during puberty. Lack of knowledge and awareness about anemia prevention is a primary factor influencing adolescents' behavior in maintaining their health status. The utilization of engaging and interactive educational media, such as animated videos and digital literacy-based media (Canva), can be an effective strategy in improving anemia prevention behavior among adolescents. This study aims to determine the effect of anemia prevention education through a combination of animated video media and digital-based literacy media (Canva) on the behavior of adolescent girls at SMAN 1 Marisa. This study employed a quasi-experimental design with a pretest-posttest approach without a control group. The sample consisted of 196 adolescent girls from grades X and XI, selected using proportional random sampling technique. The instrument used was an anemia prevention behavior questionnaire that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant increase in anemia prevention behavior in the aspects of knowledge (p = 0.000), attitude (p = 0.000), and action (p = 0.000) after the educational intervention. The conclusion of this study states that anemia prevention education using a combination of animated videos and digital-based literacy media (Canva) has an impact on the behavior of adolescent girls at SMAN 1 Marisa, in terms of knowledge, attitudes, and actions. The use of engaging and easily accessible educational media can be an alternative in health promotion among adolescents.